2004
DOI: 10.1038/sj.ijo.0802551
|View full text |Cite
|
Sign up to set email alerts
|

Excess gains in weight and waist circumference associated with childbearing: The Coronary Artery Risk Development in Young Adults Study (CARDIA)

Abstract: OBJECTIVE:To examine the association of childbearing with weight and waist circumference (WC) changes, we compared women with and without pregnancies or births during follow-up. STUDY DESIGN: A multicenter, longitudinal observational study over 10 years. Comparison groups defined by the number of pregnancies and births during follow-up: P0 (0 pregnancies; nongravid), P1 (1 þ miscarriages or abortions; 'short' pregnancies), B1 (1 birth), and B2 (2 þ births). Mean changes in weight and WC for P1, B1 and B2 group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
230
5
11

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(258 citation statements)
references
References 38 publications
12
230
5
11
Order By: Relevance
“…A third of US women aged 20-39 years are obese [1], and many women experience significant weight gain with pregnancy [2][3][4]. Due to increased risk of pregnancy complications and obesity in offspring [5][6][7][8][9][10], women of childbearing age need efficacious and accessible lifestyle interventions [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…A third of US women aged 20-39 years are obese [1], and many women experience significant weight gain with pregnancy [2][3][4]. Due to increased risk of pregnancy complications and obesity in offspring [5][6][7][8][9][10], women of childbearing age need efficacious and accessible lifestyle interventions [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Compared with weight gain during other periods of life, excess weight retained after giving birth appears to be particularly harmful, as evidence suggests that it is deposited preferentially in central rather than peripheral sites. 3,4 Postpartum weight retention is defined as the difference between weight at some time after delivery and weight prior to pregnancy. Previous studies indicate that mean postpartum weight retention is approximately 0.5 to 1 kg at 12 months, with a wide range of weight changes from more than 10 kg lost to more than 20 kg gained.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive pregnancy weight gain has been shown to lead to long term weight retention in studies of several different groups of women, among them White, middle income women (Rooney & Schauberger, 2002), adult women of various ethnicities (Gunderson et al, 2000;Gunderson et al, 2004), and also Black adolescents (Groth, 2008). Rooney and Schauberger, who followed 484 women longitudinally for 15 years (Rooney, Schauberger, & Mathiason, 2005), found that women who did not lose the weight gained during pregnancy by 6 months postpartum were 5.9 kg heavier 8-10 years later than the women who had lost the weight during the first months following childbirth.…”
Section: Previous Studies Of Weight Retention Postpartummentioning
confidence: 99%
“…If women gain weight during pregnancy according to the Institute of Medicine (IOM) recommendations, but fail to lose the extra weight by 6 months postpartum, they experience long term weight increases (Rooney & Schauberger, 2002). In addition, pre-pregnant body mass index (BMI) has also been shown to contribute to long term obesity, because women who start pregnancy heavier retain more weight following childbirth (Gunderson et al, 2004;Linne, Dye, Barkeling, & Rossner, 2003).…”
Section: Introductionmentioning
confidence: 99%